The Efforts to Improve Mathematics Learning Outcomes in Sequences and Series Materials Using a Problem Based Learning Model with a Differentiated Strategy - Khairani, Neneng; Muslimin, Muslimin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The failure to integrate differentiated learning in the classroom is the driving force behind this research. Mapping students’ learning needs is the first step in implementing individualized instruction in the classroom. Learning readiness, student interests, and learning profiles are three views on differentiated learning that can be used to map out students’ requirements. The purpose of this study is to enhance student learning experiences and results. Two devices are used for data collection: learning achievement exams and student activity observation sheets. Both descriptive statistical analysis and descriptive analysis were used to analyse the data. The average class score was 74 in the first cycle and improved to 84.4 in the second. Every student was able to meet the 75-point Minimum Completeness Criteria (KKM) set by the school. It is possible to enhance student learning activities and outcomes by combining differentiated learning with the Problem Based Learning model, according to the study’s findings. In addition to offering a learning environment that puts students’ needs first, problem-based learning activities also benefit formative and summative learning through the third step of differentiation.